On differential rational invariants of classical motion groups - Bekbaev, Ural; Rakhimov, Isamiddin; Muminov, Qabuldjan (World Scientific Publishing Company, 2015)
A pure algebraic approach to differential invariants of curves and surfaces is presented. By the use of this approach the explicit formulae for the generating differential invariants and invariant differential operators for the generic curves in n-dimensional classical geometries are considered.